Age-Dependent Changes in Bone Architecture, Patterning, and Biomechanics During Skeletal Regeneration - Hoffseth, Kevin; Busse, Emily; Jaramillo, Josue; Simkin, Jennifer; Lacey, Michelle; Sammarco, Mimi C. (Frontiers in Cell and Developmental Biology, 2021)
Mouse digit amputation provides a useful model of bone growth after injury, in that the injury promotes intramembranous bone formation in an adult animal. The digit tip is composed of skin, nerves, blood vessels, bones and tendons, all of which regenerate after digit tip amputation, making it a powerful model for multi-tissue regeneration. Bone integrity relies upon a balanced remodeling between bone resorption and formation, which, when disrupted, results in changes in bone architecture and biomechanics, particularly during aging. The goal of this study was to evaluate regenerated bone architecture and biomechanics in the context of aging. Here we use recently developed bone architecture analysis techniques to evaluate patterning differences between young and aged regenerated bone and show that regenerated bone architecture in aged mice shows vastly altered trabecular spacing and patterning. Surprisingly, we also found that tissue mineral density is increased in regenerated bone and that aging exacerbates this increase in density. We tested the biomechanics of regenerated bone in aged mice using nanoindentation which identified an overall decrease in the elasticity of aged bone. These results highlight distinct architectural and biomechanical differences in young and aged regenerated bone and provide a new predictive analysis tool for the digit amputation model to aid in evaluating the outcomes for potential therapeutic treatments to promote regeneration.